Managing Patient Deterioration : Enhancing Nursing Students' Competence Through Web-Based Simulation and Feedback Techniques : Final Report. - Cooper, Simon; Bogossian, Fiona; Cant, Robyn; Porter, Jo (Office for Learning and Teaching, 2014)
Final report from a project that focused on improving nursing students' management of patient deterioration. Hospitalized patients who experience physiological deterioration are frequently mismanaged, and there are growing international concerns over their safety. Following a series of pilot studies examining the performance of nurses/ midwives in simulated settings, the research team identified significant deficits in clinical performance1-3. Based on these experiences we have developed a provisional program of learning FIRST2ACT (Feedback Incorporating Review and Simulation Techniques to Act on Clinical Trends) which in a recent nursing trial, using time series analysis, had a significant impact on clinical practice. However, the team do not fully understand students' clinical decision strategies and best practice educational approaches, and in its present delivery model FIRST2ACT is resource intensive. This project aims to address these issues through collaboration with Universities and TAFE sector partners to produce an evidence-based, sustainable on-line learning program called FIRST2ACT Web.